Prawne aspekty przeciwdziałania marnowaniu żywności - Leśkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2015)
This article tackles wastage of food and aims to evaluate whether the currently bind-ing and applicable regulations as well as the planned ones are or will be capable of coun-teracting this phenomenon effectively. The reasons why food is wasted are discussed and related subjects identified. It is concluded that although the existing regulation is adequate-ly constructed and allows for food assistance to those in need in acompliance with the un-derstanding of resolution 223/14, i.e. using it as a tool in the battle against food wastage, the legal regulation of the phenomenon and many related areas remain underregulated and are unsatisfactory. There is a chance though that the new Act on Counteracting Food Wastage that is being drafted, despite some shortcomings, will help to improve the situation.

L’oggetto delle considerazioni è una problematica giuridica riguardante il contrasto agli sprechi alimentari, invece il loro obiettivo mira a formulare una valutazione prelimi-nare riguardo alla domanda se le soluzioni giuridiche esistenti e progettate siano efficaci nel contrastare il fenomeno in oggetto. L’autrice dibatte le cause di spreco alimentare ed indica anche gli enti ai quali questo fenomeno viene associato. Nella parte conclusiva essa sostiene che il legislatore si serve molto abilmente del concetto di aiuto alimentare ai bisognosi ai sensi del regolamento n. 223/14 in qualità di “strumento” di lotta contro lo spreco alimentare perché associa politiche di lotta alla povertà con il fenomeno di ecce-denze alimentari, quindi di spreco alimentare. Le soluzioni introdotte nel regolamento n. 223/14 meritano un giudizio favorevole. Se si tratta invece di legislazione, tante aree connesse alla problematica in esame rimangono tuttora non disciplinate in modo soddis-facente. La legge sulla prevenzione dello spreco alimentare può, nonostante certe lacune, servire ad arginare il fenomeno in esame.
Legal aspects of counteracting wastage of food
Aspetti giuridici in materia di contrasto agli sprechi alimentari